PERILAKU MINUM MINUMAN KERAS PADA REMAJA DI DESA RAWANG KAWO KECAMATAN LUBUK DALAM KABUPATEN SIAK - ", Efrizal; ", Syafrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Drinking Behavior-Liquor On Teens In Rawang village Kawo Siak District of Lubuk InThis research was conducted at the Rawang Kawo Siak District of Lubuk In the aim to, among others: To find out what the background for teenagers behave consume liquor in the village of Kawo Rawang District of Lubuk In Siak. To know the effect of adolescents who consume liquor in the village of Kawo Rawang District of Lubuk In Siak.This research is a qualitative descriptive, citizens, sellers of alcohol on adolescent drinking activism. The technique used Accedental sampling of respondents happened to be in the field, further Similarly samapai using the method of observation, documentation, and in-depth interviews using the interview guide in analyzing the research data used in the analysis kualituliatif and descriptive writing in the manner described.Based on the results of this study concluded that the melatarbelangi drinking behavior is the influence of family environment and the influence of friends.Keywords: Behavior In Teens, Drinking-Liquor